2000
DOI: 10.1046/j.1365-2591.2000.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed Nd:YAG laser irradiation on smear layer at the apical stop and apical leakage after obturation

Abstract: These results suggest that pulsed Nd:YAG laser irradiation with black ink increases the removal of smear layer compared with that without black ink, and reduces apical leakage after obturation significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 27 publications
1
24
1
11
Order By: Relevance
“…15 Laser has changeable parameters, so different results can be gained. [46][47][48] Power is one of those parameters. According to the study by Takeda et al the power of 1/2 W is adequate for clearing the smear layer, 11,49,50 moreover, the power of 1/2 W is adequate for disinfecting the canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Laser has changeable parameters, so different results can be gained. [46][47][48] Power is one of those parameters. According to the study by Takeda et al the power of 1/2 W is adequate for clearing the smear layer, 11,49,50 moreover, the power of 1/2 W is adequate for disinfecting the canal.…”
Section: Discussionmentioning
confidence: 99%
“…But it should be considered that due to higher absorption of Er:YAG laser's energy by water in comparison with other lasers such as Nd:YAG and CO 2 , the possibility of increasing temperature is minimum. 48 Water or air sprays are some of the efficient factors in preventing thermal damage. [49][50][51] The study by Theodoro et al showed that applying laser for 30 seconds with water spray can decrease temperature (-2.2 ± 2.5°C).…”
Section: Anti-bacterial Effect Of Er:yag Laser On Enterococcus Faecalismentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In view of ''dentin melting'' 8 and ''reduction of the permeability of dentin'', 3 a number of investigators have attempted to improve the quality of the apical seal and thus to reduce apical leakage after apical filling. [9][10][11][12][13][14][15] It is clear from these studies that morphologic changes after Nd:YAG laser irradiation can influence the marginal sealing of the root-canal obturation. Data evaluating coronal leakage of root fillings after laser irradiation of the root-canal walls remain scarce.…”
mentioning
confidence: 99%
“…GOYA et al 27 , em 2000, tiveram como objetivo avaliar a remoção da "smear layer" pelo laser Nd:YAG, quando da utilização de tinta nanquim ou não, e a infiltração apical após a obturação do sistema de canais radiculares.…”
Section: Revisão De Literatura 21unclassified
“…Este resultado está de acordo com o trabalho de GOYA et al 27 , que concluíram que a irradiação das paredes dos canais radiculares com laser Nd:YAG, principalmente com a associação à tinta nanquim, reduziu de forma significativa a infiltração apical de canais obturados. Os autores concluíram ainda, que a parede dos canais irradiada pelo laser, apresentava-se sem "smear layer", evidenciando superfícies com túbulos dentinários abertos e em outra parte a "smear layer" se apresentava derretida e aderida à dentina, obliterando os túbulos dentinários.…”
Section: Grupounclassified